The State in Contemporary Arab political Thought - Mandel , Lecurer .Yathrib khatib (The International and Political Journal, 2023)
There are many concepts and terms that attempt to clarify the concept of the state in contemporary Arab political thought. Despite the simplicity that characterizes the definition of the state and the research into determining the origin of its establishment and the basis of authority within it, the definition raises, in reality, a wide number of problems. The state is a political reality because any Arab society consists of political units, each of which bears the title of state, and the state also has a legal concept for the purpose of regulating the relationship between political units that are unequal in power on the basis of justice and equality. The state, at the same time, is an abstract philosophical idea because the existence of organized political societies is not known historically. In the absence of this historical knowledge, there are theories or ideas of a philosophical nature that attempt to explain the emergence of the state and the emergence of its pillars, considering that the state is a social entity whose most important components are the individuals who are united by special ties that make them capable of living together.